The Role of Novelty as an Objective Condition in the Quality of Invention - Abdessemed, Rima; Messaour, Djalila (Journal of Legal Studies and Researches, 2021)
The patent stimulates technical growth and economic progress. Whether the invention is a new product or method. The novelty of the invention is one of the objective conditions, meaning that the invention has not been presented to the public before, but the novelty of the invention resulting from the new method raises many questions about the quality of the old recycled product that holds a new patent and the extent of this impact on development.